(untitled) (Fiep Bulletin - online, 2011)
The objective of the present study is to analyze the motor performance of girls chronologically aged between 09 to 13, from the Quilombo of Curiaú community, using the menarche as discretionary parameter. The sample composed of 31 volunteershas been selected in a non-probabilistic and intentional voluntary way. For setting of the maturation the Questionnaire of Sexual Maturation has been used (OLIVEIRA JÚNIOR, 1996). The collection of anthropometric data of Height and Body Mass and the following tests were accomplished: Horizontal Jump; medicine ball throw; 20 meters race; Shuttle-Run. The results showed that the average annual growth of the group corresponds to 5,63 cm, more expressive between 10 and 11 year-olds (12,72 cm). The same happens with Body Mass (BM) average progressive increment of 6,29 kg, more expressive between 10 and 11 year-olds (10,86 kg). The Average Age of Menarche (AAM) of the group was 11,44 years old and none of the girls has presented menarche before 11 years old, being inferior to the studies accomplished in other areas of the country. BMI values found are according to healthy patterns. During the tests, there were good results for Lower Limbs Strength (IMS), but, especially the Agility, has been below the average. The scores have been ascending way, and the most expressive ones obtained in the 11-12 year-olds, with evident descent soon after, what has support in literature (GUEDES & GUEDES, 1993; GUEDES & BARBANTI, 1995). The medium scores are superior in the menarched girls in relation to Non menarched concerning the relative parameters to the motor performance, which indicates that the maturation has caused impact in the results of the motor tests.